In vitro assessment of dual‐network electrospun tubes from poly(1, 4 cyclohexane dimethylene isosorbide terephthalate)/PVA hydrogel for blood vessel application. Issue 12 (18th November 2018) - Khan, Muhammad Qamar; Kharaghani, Davood; Nishat, Nazish; Sanaullah,; Shahzad, Amir; Yamamoto, Takayuki; Inoue, Yuma; Kim, Ick Soo
ABSTRACT: The fabrication of artificial blood vessel remains an ongoing challenge for cardiovascular tissue engineering. Full biocompatibility, proper physiological, and immediate availability have emerged as central issues. To address these issues, the dual‐network composite scaffolds were fabricated by coating the electrospun nanofibers‐based tubes with poly(vinyl alcohol) (PVA) hydrogel, which could increase the cell viability and show the potential for controlling the composition, structure, and mechanical properties of scaffolds. Herein, the tubular scaffolds having an inner diameter of 2 mm, were composed with poly(1, 4 cyclohexane dimethylene isosorbide terephthalate)/PVA. The morphology examination showed that tubular structure was dimensionally stable and suitable for an artificial blood vessel. Fourier transform infrared spectra, wetting behavior, stress–strain behavior, and Thiazolyl Blue Tetrazolium Bromide (3‐(4, 5‐dimethylthiazol‐2yl)‐2, 5‐diphenyltetrazolium bromide) analysis also showed that the composite scaffolds have good chemical interactions between poly(1, 4 cyclohexane dimethylene isosorbide terephthalate) (PICT) and PVA, blended PICT/PVA tubes showed the appropriate wetting behavior, it achieved the appropriate breaking strength and adequate pliability up to 47.5% and in vitro assessment showed that blended PICT/PVA scaffolds have the appropriate cell viability and nontoxic, respectively. On the basis of characterizations results, it was concluded that resultant scaffolds would be addressed to fulfill the requirements such as biocompatibility, dimensional stability, adequate elongation, breaking strength, immediate availability, and proper for physiologically. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47222. Abstract : The dual‐network composites are fabricated by coating the poly(1, 4 cyclohexane dimethylene isosorbide terephthalate) (PICT) electrospun nanofibers tubes with poly(vinyl alcohol) (PVA) hydrogel. The resultant scaffolds show the appropriate breaking strength up to 3 ± 0.5 MPa and adequate pliability up to 47.5 ± 3%. The in vitro assessment of PICT/PVA composites with fibroblast cells show the appropriate cell viability and nontoxicity for human beings. The resultant scaffolds fulfill the stated and implied needs of a blood vessel with respect to biocompatibility, adequate elongation, and breaking strength, composition, and dimensional stability.